Apolipoprotein E polymorphism and its association with biochemical markers of diabetes mellitus - Rahman, Hafizur K.M (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2013)
Apolipoprotein E gene (APOE) has been known for more than 30 years and has been widely studied around the world for its role in the pathogenesis of diseases that are closely related to lipid and lipoprotein metabolism. Studies regarding the association between the APOE gene and type 2 diabetes mellitus (T2DM) are scarce. Therefore, this case-control study was aimed to investigate APOE allelic frequencies among the diabetic and non-diabetic subjects and associations between the alleles and selected bio-chemical markers between them. A total of 102 subjects were recruited, 51 were diabetic, and 51 were non-diabetic. Their fasting blood samples were analyzed for fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL). Restriction Fragment Length Polymorphism technique was used to identify the APOE alleles. Statistical analyses were performed using the Predictive Analytics SoftWare (PASW) Statistics, Version 18.0. Frequencies of the 2 and 4 alleles were slightly higher, and the 3 allele was slightly lower in the diabetic group compared to the non-diabetic group (12.7% vs 8.8%, 24.5% vs 22.6%, and 62.8% vs 68.6% respectively). Diabetics with 2 allele had the highest mean values of all selected bio-chemical markers, and the trend was followed by 4 and 3 alleles. Both the 2 and 4 allelic diabetic subjects had significantly higher FBG compared to the 3 allelic diabetic subjects (10.11 vs 8.18 and 9.89 vs 8.18 mmol/L respectively, p<0.05). In contrast, diabetic subjects with 2 and 4 alleles had significantly higher TC (6.57 vs 4.58 and 5.41 vs 4.07 mmol/L respectively, p<0.05) while only  allelic diabetic subjects had significantly higher TG (1.57 vs 0.97 mmol/L, p<0.05) compared to the non-diabetic subjects. In conclusion, the APOE gene polymorphism influences blood levels of the selected bio-chemical markers in subjects with T2DM.